Temperature-dependent diffusion coefficient of oil from different sunflower seeds during extraction with hexane - Perez, Ethel (2011)
Oil extraction from confectionery, oilseed and wild sunflower seeds with n-hexane was investigated by laboratory tests carried out in a stirred batch extractor at several temperatures (40, 50 and 60 °C). The rates of extraction were determined from ground sunflower seeds (particle sizes between 0.420 and 1.000 mm). The oil yield in the extract increased with higher contact time and extraction temperature in all the cases. Equilibrium constants at 50 °C for different solvent-ground seed ratios are reported. A mathematical model of oil extraction from seeds of sunflowers, based on a modified diffusive process in spherical geometry of particles, was proposed. The analysis of significance of the coefficient of fitting regression models showed significant differences between temperatures for each genotype and between genotypes at each temperature. The resulting diffusion coefficient ranged from 1.34 × 10-12 to 1.87 × 10-12 m2/s for confectionery, 2.06 × 10-12 to 5.03 × 10-12 m2/s for oilseed, and 9.06 × 10-13 to 1.18 × 10-12 m2/s for wild sunflower. The temperature dependence of the diffusion coefficient was represented by an Arrhenius-type equation for each sunflower seed studied. Activation energy values of 13.74, 33.95 and 11.32 kJ/mol were obtained for confectionery, oilseed and wild sunflower, respectively.